Influência da precipitação pluviométrica para as estruturas limnológica e microbiológica da bacia hidrográfica do Ribeirão Cafezal - Piacenza, Larissa Baptistuci (2021)
The Cafezal stream water supply basin is one of the main water sources in the city of Londrina-PR. With its source in the city of Rolândia, traveling through the municipality of Cambé-PR, until the SANEPAR catchment station in Londrina-PR, it travels through urban and rural areas, crossing different landscapes and land uses. In order to assess the influence of precipitation on the limnological and microbiological structures of the basin, the historical rainfall and fluviometric series were elaborated, and limnological indicators (hydrogen potential, dissolved oxygen, electrical conductivity, suspended solids and water temperature) and microbiological (total coliforms, Escherichia coli and heterotrophic bacteria). Thematic charts were drawn up to verify whether the geographic conditions of the basin and land use have an influence on the monitored indicators. Finally, statistical tests (PERMANOVA and Principal Component Analysis) were applied to test the correlation and variance between the data collected. Permanova demonstrated, in general, that spatial variation is not a segregation factor of limnological and microbiological structures, but that they are influenced by the rainfall regime. The PCA corroborated the permanova result and demonstrated that limnological and microbiological structures vary significantly according to the rainfall regime, especially the variables dissolved oxygen, ranging from 10.92 mg/L in the period with the lowest rainfall volume to 27.42 mg/L in the period with the highest rainfall volume; E.coli, ranging from 1.08 x 10³ CFU in the period with the lowest rainfall volume to 6.2 x 10³ CFU in the period with the highest volume of temperature rainfall; pH, ranging from 6.87 in the period with the lowest rainfall volume to 6.78 in the period with the highest rainfall volume; total coliforms, ranging from 9.2 x 10³ CFU in the period with the lowest rainfall volume to 2.1 x 104 in the period with the highest rainfall volume; hetrottrophic bacteria, ranging from 2.13 x 104 CFU in the period with the lowest rainfall volume to 2.0 x 105 in the period with the highest rainfall volume; and suspended solids, ranging from 99.33 mg/L in the period with the lowest rainfall volume to 37.27 mg/L in the period with the highest volume of rainfall.